2015
DOI: 10.1037/hea0000106
|View full text |Cite
|
Sign up to set email alerts
|

Weight stigma mediates the association between BMI and self-reported health.

Abstract: Objective Weight stigma is pervasive in the United States. We tested the hypothesis that stigma may be a mechanism through which obesity negatively affects self-reported health. Two studies examined whether perceived weight-based discrimination and concerns over weight stigma mediated the association between BMI and self-reported psychological health (Study 1) and physical health (Study 2). Method In two online studies, adult community members completed measures of stigma-relevant mediators (perceived weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
132
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(145 citation statements)
references
References 24 publications
11
132
1
1
Order By: Relevance
“…Consistent with recent findings on adults (Hunger & Major, 2015), the current findings indicate that the connection between heavy weight and emotional adjustment is largely due to perceived weight discrimination. At 7 th grade, it was weight-based peer discrimination rather than concurrently assessed BMI that predicted body dissatisfaction, social anxiety, and loneliness by 8 th grade.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with recent findings on adults (Hunger & Major, 2015), the current findings indicate that the connection between heavy weight and emotional adjustment is largely due to perceived weight discrimination. At 7 th grade, it was weight-based peer discrimination rather than concurrently assessed BMI that predicted body dissatisfaction, social anxiety, and loneliness by 8 th grade.…”
Section: Discussionsupporting
confidence: 92%
“…Weight-based peer mistreatment, in turn, is concurrently associated with lower self-esteem and elevated depression, over and above actual weight (i.e., body mass index, BMI) (Eisenberg, Neumark-Sztainer, & Story, 2003; Eisenberg, Neumark-Sztainer, Haines, & Wall, 2006). These findings are consistent with recent research on adults suggesting higher BMI is indirectly related to concurrent psychological and physical health through perceived weight discrimination (Hunger & Major, 2015; Rosenthal et al, 2015). The latest evidence on adults also suggests that weight-discrimination might be an even more potent predictor of health than other attributions for discrimination (Sutin, Stephan, & Terracciano, 2015).…”
supporting
confidence: 92%
“…Research from other large-scale epidemiological studies has likewise shown that experiencing weight-based mistreatment is associated with lower self-acceptance, a construct analogous to self-esteem (Carr & Friedman, 2005). Hunger and Major (2014) found that weight stigma mediated the negative relationship between BMI and psychological wellbeing (i.e., self-esteem, depression, and quality of life). Interestingly, concerns about stigma emerged as a stronger predictor of health than did perceptions of discrimination, although these two components of weight stigma were strongly correlated.…”
Section: Weight Stigma Compromises Psychological Healthmentioning
confidence: 95%
“…Indeed, many of the psychological effects routinely attributed to carrying excess weight – such as low self-esteem, greater depression and anxiety, and poorer quality of life – result more from the stigma faced by overweight individuals than from the weight itself (Carr, Friedman, & Jaffe, 2007; Hunger & Major, 2014). Hatzenbuehler, Keyes, and Hasin (2009) performed a comprehensive analysis of the effects of perceived weight discrimination on mental health.…”
Section: Weight Stigma Compromises Psychological Healthmentioning
confidence: 99%
“…Interestingly, low body-and self-esteem occurs less among OW/obese black girls and women, who generally report a higher quality of life (QOL) than white women. OW/obese children are more likely to be bullied by others and are less likely to participate in physical activities adding to the likelihood of obesity-related complications [24,25]. Stigma and weight discrimination may mediate some of the poor health outcomes that are related to increased BMI, but additional research is needed [26].…”
Section: Psychosocial Consequencesmentioning
confidence: 98%